(untitled) (Baghdad Science Journal, 2025)
As the bit rate of fiber optic transmission systems is increased to more than , the system will suffer from an important random phenomena, which is called polarization mode dispersion. This phenomenon contributes effectively to: increasing pulse width, power decreasing, time jittering, and shape distortion. The time jittering means that the pulse center will shift to left or right. So that, time jittering leads to interference between neighboring pulses. On the other hand, increasing bit period will prevent the possibility of sending high rates. In this paper, an accurate mathematical analysis to increase the rates of transmission, which contain all physical random variables that contribute to determine the transmission rates, is presented. Thereafter, new mathematical expressions for: pulse power, peak power, time jittering, pulse width, and power penalty are derived. On the basis of these formulas, one can choose a certain operating values to reduce or prevent the effects of polarization mode dispersion.